Optimization of Nostril Breathing Exercises as a Complementary Therapy in Hypertension Management - Dian Istiana; Dewi Nur Sukma Purqoti; Supriyadi Supriyadi (Yayasan Lentera Mitra Lestari, 2026)
Background: Hypertension or high blood pressure is a medical condition characterized by consistently high arterial blood pressure. If left untreated, hypertension can increase the risk of heart disease, stroke, kidney failure, and other health problems. Hypertension management can include complementary practices such as Alternate Nostril Breathing exercises. Aims: To determine the effect of alternate nostril breathing on reducing blood pressure in the elderly with hypertension in the Karang Buyuk area, South Ampenan Subdistrict. Method: A pre-experimental method was conducted. The research design used a one-group pretest-posttest design. The population consists of all elderly women in the Karang Buyuk area. The sample size in this study was 16 respondents, and the sampling technique used was purposive sampling. Data analysis was conducted using a paired t-test, and the instruments used were observation sheets: standard operating procedure for alternate nostril breathing exercises, and a sphygmomanometer. The intervention was administered for 2 weeks. Result: Based on the data, the majority of respondents were aged 60-74 years (12 respondents (75%)); most respondents were unemployed 10 (62.5%)); most respondents had an elementary school education (7 respondents (43.75%)); mean systolic pretest 152.13 and mean systolic posttest 144.25. The data analysis showed a significance value of 0.000 (< 0.05), indicating a reduction in blood pressure after performing alternate nostril breathing exercises. Conclusion: There is an effect of alternate nostril breathing on reducing blood pressure in the elderly with hypertension.